LEGAL DUE TO CANCELLATION OF SALE AND PURCHASE ASSETS THAT DO NOT MEET THE MATERIAL AND FORMAL CONDITIONS - Rendy Renaldy (University of Sang Bumi Ruwa Jurai, 2020)
The focus of this study is the implementation of the cancellation of authentic deeds that do not meet the material requirements and formal requirements as well as the legal consequences of the cancellation of the binding deed of sale and purchase that do not meet the material requirements and formal requirements. The method used in this study is the normative approach and the Normative approach is derived from data collection obtained from primary data and secondary data, then analyzed by qualitative analysis methods. The answer to the problem in this study is that the implementation of authentic deed cancellation that does not meet the material requirements and formal requirements, the injured party can make an effort to settle the cancellation of the deed that is a court suit. The evaluation of a notarial deed becomes null and void by law must go through a lawsuit process to the general court to prove whether the notary deed violates the provisions in the UUJN or other legislation. If there is a party who believes or knows that the notarial deed violates the applicable provisions, the parties must be able to prove it through a lawsuit in court.